2002
DOI: 10.1128/jvi.76.7.3095-3104.2002
|View full text |Cite
|
Sign up to set email alerts
|

Novel Swine Virulence Determinant in the Left Variable Region of the African Swine Fever Virus Genome

Abstract: Previously we have shown that the African swine fever virus (ASFV) NL gene deletion mutant E70⌬NL is attenuated in pigs. Our recent observations that NL gene deletion mutants of two additional pathogenic ASFV isolates, Malawi Lil-20/1 and Pr4, remained highly virulent in swine (100% mortality) suggested that these isolates encoded an additional virulence determinant(s) that was absent from E70. To map this putative virulence determinant, in vivo marker rescue experiments were performed by inoculating swine wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 50 publications
3
70
0
1
Order By: Relevance
“…On the other hand, significant differences exist in pMGF 110-2L, -9L and, to a esser extent, p86R, which could lead to lower virulence. A study with isolates lacking all MGF 110 members suggested that these may neither be essential for replication nor have a role in virulence (Agüero et al, 1990 Burrage et al, 2004;Neilan et al, 2002;Zsak et al, 2001). In Vero cell-adapted Ba71V, also with a deletion of 8.2 kb in this area of the genome, replication in macrophages was restored after the introduction of consecutive 3CL, 3DL and 3EL (MGF 360-9L, -10L and -11L, respectively); 3FR (MGF 505-1R); and 3HL, 3IL and 3LL (MGF 360-12L, -13L and -14L, respectively) (Zsak et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, significant differences exist in pMGF 110-2L, -9L and, to a esser extent, p86R, which could lead to lower virulence. A study with isolates lacking all MGF 110 members suggested that these may neither be essential for replication nor have a role in virulence (Agüero et al, 1990 Burrage et al, 2004;Neilan et al, 2002;Zsak et al, 2001). In Vero cell-adapted Ba71V, also with a deletion of 8.2 kb in this area of the genome, replication in macrophages was restored after the introduction of consecutive 3CL, 3DL and 3EL (MGF 360-9L, -10L and -11L, respectively); 3FR (MGF 505-1R); and 3HL, 3IL and 3LL (MGF 360-12L, -13L and -14L, respectively) (Zsak et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal regions of members of MGFs 300, 360 and 505/530 share significant similarity with each other (Yozawa et al, 1994). Several genes in MGF 360 and 505/530 determine host range and virulence (Afonso et al, 2004;Neilan et al, 2002;Tulman & Rock, 2001). It has also been observed that repeated passage of field isolates of ASFV through tissue culture results in the loss of members of the MGF 110 family (Almendral et al, 1990;de la Vega et al, 1990;Pires et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Using restriction endonuclease digestion, the authors demonstrated the existence of different lengths of SmA1 and EcoR-I restriction fragment patterns as a probable consequence of deletion or genetic rearrangement of the virus genome. Furthermore, it was demonstrated that variation in length of restriction fragments can be associated with virulence (NEILAN et al, 2002). A high level of variability in the virulence of ASFV field isolates from inside and outside Africa was demonstrated by restriction length fragment polymorphism (RFLP).…”
Section: Asfv Population Virulence Heterogeneity In Brazilian Outbreaksmentioning
confidence: 99%
“…The ASFV genome is a DNA molecule which contains a central conserved region and variable terminal regions composed of internal inverted complementary repetitions arranged in tandem, including the five multigene families (MGF 100, 110, 300, 360 and 505/530) where genetic variation mainly occurs (CHAPMAN et al, 2008). The genetic variability of several genes associated with virulence and host range suggested that low virulence could be associated with a decrease in the number of genes in families 360 and 505/530 following mutations with large deletions (CHAPMAN et al, 2008;NEILAN et al, 2002;TULMAN;ROCK, 2001). …”
Section: Asfv Population Virulence Heterogeneity In Brazilian Outbreaksmentioning
confidence: 99%
See 1 more Smart Citation